MORPHOLOGICAL CASTE DIFFERENCES IN POLYBIA AEQUATORIALIS (HYMENOPTERA: VESPIDAE: POLISTINAE: EPIPONINI), A SOCIAL WASP of THE HIGHLANDS of COSTA RICA - Chavarria Pizarro, Laura [UNESP]; Alvarado, Mauricio Roverssi [UNESP]; Noll, Fernando Barbosa [UNESP] (New York Entomological Soc Inc, 2009)
Many aspects of the biology and organization of Neotropical social wasps in the highlands are unknown. Polybia aequatorialis is a highland wasp of Costa Rica distributed between 1, 150 and 3,200 m in altitude, and little information on this species is recorded. We investigated the size of a colony of P. aequatorialis in the Cerro de la Muerte region of Costa Rica, and studied the morphological differences between queens and workers. Measures were taken from 248 reproductive and non-reproductive females, and caste differentiation was analyzed by Discrimination Function Analysis. We did not find a highly pronounced caste distinction in P. aequatorialis, even though ANOVA showed that queens and workers differed in all morphometric measures. The morphological differences between the reproductive and non-reproductive females probably results from a developmental switch, which is a characteristic caste syndrome of Polybia.
Keywords: Polistinae; Epiponini; Polybia aequatorialis; colony size; Caste difference